Gender and multilingual bias in observations of children with a developmental language disorder - de Vries, Jitske; van der Velde, Max; Veldkamp, Bernard; Hakvoort, Britt; Bulder, Ebbo; Essen, Aafke; Schildkamp, Kim (Frontiers in Psychology, 2025)
PurposeThe aim of our study was to clarify DLD characteristics specific to boys and girls and monolingual and multilingual children, including the detection of possible bias in observations made by speech-language therapists.MethodsWe used text-mining techniques on existing individual treatment plans for children diagnosed with DLD (N = 994) written by speech-language therapists. Specific analyses included analyses of unigrams, bigrams, and trigrams within lines (N = 9,092) of individual treatment plans, followed by sentiment analyses of these unigrams, bigrams, and trigrams.ResultsNot only were girls described with more negative words but the focus of the identified DLD characteristics also differed. Boys were described more in terms of tasks and girls in terms of personal characteristics, specifically hearing problems. Multilingual children were described far more negatively by their speech-language therapists than monolingual children, combined with what appeared to be a somewhat stronger focus on vocabulary in observations.ConclusionThe found differences can be due either to bias or actual differences in characteristics between these groups. Screening procedures should be adapted to detect these children earlier, and speech-language therapists should be made aware of the differences in their observations of girls and multilingual children with DLD to avoid bias.